Lightning Prediction Using Electric Field Measurements Associated with Convective Events at a Tropical Location - Jana, Soumyajyoti; Chakraborty, Rohit; Maitra, Animesh (Pure and applied geophysics, 2023)
Nowcasting of lightning occurrences is essential in tropical locations as lightening causes severe damage to life and property. This study attempts to nowcast lightning events during convective phenomena using an electric field monitor (EFM) at a tropical urban location, Kolkata (22.65°N, 88.45°E). Before the onset of heavy lightning occurrences, definite changes in the atmospheric electric field (EF) are observed, which in turn are associated with high cloud liquid water content (LWC) and low cloud base height (CBH). A model has been proposed to nowcast lightning strikes within about 17.5 km radius of the present location based on the EF standard deviation (EFSD) values. The proposed technique is tested with the lightning data provided by a collocated lightning detector, which yields a prediction efficiency of ~ 0.91 (~ 0.86), a false alarm rate of ~ 0.23 (~ 0.18), and a critical success index of ~ 0.71 (~ 0.72) with an optimal range of other performance parameters during the monsoon (pre-monsoon) periods, thereby generating an alarm 45 min before lightning events.